2021
DOI: 10.1099/mgen.0.000539
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and transmission of Mycobacterium bovis in Ethiopia

Abstract: Bovine tuberculosis (bTB) is endemic in cattle in Ethiopia, a country that hosts the largest national cattle herd in Africa. The intensive dairy sector, most of which is peri-urban, has the highest prevalence of disease. Previous studies in Ethiopia have demonstrated that the main cause is Mycobacterium bovis , which has been investigated using conventional molecular tools including deletion typing, spoligotyping and Mycobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 70 publications
(140 reference statements)
2
12
0
Order By: Relevance
“…The analysis of within-host diversity identified isolates from the same animal that were up to 26 SNPs apart, highlighting the likelihood of these animals suffering from mixed infections, higher rates of within-host evolution or long-term infections that are not being detected. This level of within-host diversity is similar to that observed in cattle in Ethiopia [91], although further analyses of multiple isolates from the same animals in other settings will be required to see if this is common to all animals infected with bTB. Examination of the pairwise SNP diversity amongst the defined fastBAPS clusters showed that there was much less diversity amongst cluster 1, which comprised Eu1 isolates, when compared to the other three clusters comprising Eu2 isolates which had similar levels of diversity ().…”
Section: Discussionsupporting
confidence: 58%
“…The analysis of within-host diversity identified isolates from the same animal that were up to 26 SNPs apart, highlighting the likelihood of these animals suffering from mixed infections, higher rates of within-host evolution or long-term infections that are not being detected. This level of within-host diversity is similar to that observed in cattle in Ethiopia [91], although further analyses of multiple isolates from the same animals in other settings will be required to see if this is common to all animals infected with bTB. Examination of the pairwise SNP diversity amongst the defined fastBAPS clusters showed that there was much less diversity amongst cluster 1, which comprised Eu1 isolates, when compared to the other three clusters comprising Eu2 isolates which had similar levels of diversity ().…”
Section: Discussionsupporting
confidence: 58%
“…The sports hunting industry has fueled high densities of wild boar and red deer in the Castelo Branco district, an agroforestry region, which thus may be more likely to experience transmission from wildlife, whereas in the rural settings of Portalegre, transmission involving extensively managed cattle may be more frequent. Other studies have also shown that the role of wildlife changes by location [23,[49][50][51][52][53][54]. These hypotheses are to be further demonstrated in future studies.…”
Section: Discussionmentioning
confidence: 66%
“…Raw M. bovis sequence files from Almaw et al [10], Loiseau et al [11], Orloski et al [12], Reis and Cunha [7], Rodrigues et al [13], Zwyer et al [14] and from BioProject PRJNA769553 were downloaded from the NCBI Sequence Read Archive. A full list of downloaded samples can be found in Supplemental File 1.…”
Section: Sequence Assembly and Annotationmentioning
confidence: 99%